2018
DOI: 10.1155/2018/6460393
|View full text |Cite
|
Sign up to set email alerts
|

Development of a HPLC‐MS/MS Method to Determine 11 Bioactive Compounds in Tongmai Yangxin Pill and Application to a Pharmacokinetic Study in Rats

Abstract: A sensitive and reliable HPLC-MS/MS method has been developed and validated for simultaneous determination of eleven bioactive compounds (rhein, emodin, stilbene glycoside, liquiritin, ononin, verbascoside, gallic acid, schisandrin, liquiritigenin, glycyrrhizic acid, and isoliquiritigenin) in rat plasma after oral administration of Tongmai Yangxin Pill. The collected plasma samples were prepared by liquid-liquid extraction with ethyl acetate after acidification. Eleven compounds were separated on a CORTECS™ C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Peak 50 exhibited a parent ion at m / z 283.0275 (C 15 H 8 O 6 ), displaying successive losses of 28 and 44 amu ( Figure S7 ) and annotated as trihydroxycoumestan in accordance with published data [ 39 ]. Likewise, peak 53 exhibited [M − H] − at m / z 485.1269, C 28 H 22 O 8 − ( Figure S8 ), and identified as longusol C, a stilbene dimer previously isolated from C. longus [ 31 ].…”
Section: Resultssupporting
confidence: 84%
“…Peak 50 exhibited a parent ion at m / z 283.0275 (C 15 H 8 O 6 ), displaying successive losses of 28 and 44 amu ( Figure S7 ) and annotated as trihydroxycoumestan in accordance with published data [ 39 ]. Likewise, peak 53 exhibited [M − H] − at m / z 485.1269, C 28 H 22 O 8 − ( Figure S8 ), and identified as longusol C, a stilbene dimer previously isolated from C. longus [ 31 ].…”
Section: Resultssupporting
confidence: 84%
“…TMYX, an effective patent medicine that is commonly used to treat CHD, arrhythmias, and HF, has bright clinical application prospects. With regard to the different pathophysiological factors of cardiac remodeling, previous studies of TMYX have indicated that TMYX can inhibit cardiac hypertrophy; decrease the apoptosis rate of myocardial cells; decrease anti-inflammatory, antioxidant, antiarrhythmic, and myocardial protection; promote angiogenesis; and ameliorate cardiac energy metabolism in a rat model of MI and ischemic reperfusion injury [12][13][14]. Currently, cardiac ultrasound (CUS) [5,15,16] and CMRI [5,17] are the major tools for the evaluation of ventricular remodeling and myocardial fibrosis at the international level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SIRT3 regulates mitochondrial biosynthesis by activating PGC-1α. Studies (12) have shown that myocardial protective active substances in TMYXP, the identi ed compounds are mainly derived from licorice, Schisandra chinensis, Ophiopogon. Glycyrrhizin, the main active compound of TMYXP, can activate the AMPK/SIRT1/PGC-1α signaling pathway in the kidneys of db/db mice with diabetic nephropathy in rats, and play a role in inhibiting ROS activation and apoptosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Tongmai Yangxin Pill (TMYXP) is a traditional Chinese medicine composed of 11 Chinese herbal medicines, including Radix Scutellariae, Glycyrrhiza uralensis, Radix Glycyrrhizae, Schisandra chinensis, Radix Polygonum multi orum, etc. It has the effect of nourishing the heart and nourishing the blood, tongmai analgesia, and is used for the treatment of chest pain, heartache, angina pectoris, arrhythmia, etc (12). Studies (13) have shown that the myocardial protective effect of TMYXP may be related to antioxidant effects, but its mechanism has not yet been elucidated.…”
mentioning
confidence: 99%